Influences on water source selection and use among women in rural Odisha, India - Patrick, Madeleine; Hennink, Monique; Dasmohapatra, Munmun; Rout, Manaswini; Clasen, Thomas; Caruso, Bethany A. (Frontiers in Water, 2023)
Introduction Water is a crucial resource for many household functions, including drinking, cooking, bathing, and washing clothes. Globally, women bear the burden of water collection in households without piped water, as well as responsibility for household chores that require water. Carrying water has a number of health and safety risks, and women often rely on multiple water sources. The goal of this study is to understand how women in rural Odisha, India, an area with high coverage of improved water sources, make decisions on where to collect water. Methods This is a grounded-theory, secondary analysis of qualitative data collected from 69 women across life stages in eight villages in rural Odisha. Women were asked about their concerns and difficulties related to water and probed for details in a variety of contexts, including at night, during monsoon season, and during pregnancy. Results Women's standards for water quality vary depending on the planned use of the water. They report a willingness to travel long distances to collect better tasting water for cooking and drinking. When washing clothes, they often prefer a larger body of water. Bathing or washing menstrual cloths requires privacy. Their ability to access water varies based on individual characteristics such as: life stage, as recently married women have less freedom of movement than older women; health status, as older women report difficulties carrying water long distances; cyclical patterns such as seasonality, as certain sources are inaccessible during monsoon season; and characteristics of the water and the source itself, which encompasses distance, perceived quality, and privacy, among others. Discussion These findings indicate that public health interventions and surveys that monitor household water should not only consider the presence of a water source on the premises, but should also include multiple source use and consideration of individual members of households and the time of data collection, as water sources may not be equally available or acceptable to all household members at all times. In climate-sensitive areas, multiple water source use may become increasingly necessary as a response to changes in the environment, and should be considered in climate resilience interventions.